(untitled) (Homoeopathy for All, 2025)
Polycystic Ovarian Disease (PCOD) is a common endocrine disorder that affects women of reproductive age. Characterized by hormonal imbalances, multiple ovarian cysts, and menstrual irregularities, it has far-reaching consequences on metabolic, reproductive, and psychological health. This article provides a detailed overview of PCOD, encompassing its causes, signs, symptoms, complications, and diagnostic criteria. Additionally, it explores the role of homeopathy as a holistic treatment option for managing PCOD symptoms and improving overall health.